INTRODUCTION OF TRENDS IN THE DEVELOPMENT OF PEDAGOGICAL IDEAS AND EDUCATIONAL ACTIVITIES OF UKRAINIAN WRITERS OF WESTERN UKRAINE IN EDUCATIONAL EDUCATION - Bagriy, Maria (Mountain School of Ukrainian Carpaty, 2022)
Scientific analysis of the problem of development of pedagogical ideas and educational activities of Ukrainian writers in Western Ukraine (late XVIII - 30s of the XX century) is not only relevant but also a productive area of modern historical and pedagogical research and creative pursuits of educators-practitioners. In the modern educational and pedagogical space of Ukraine there is an active search and testing of effective means of improving the education and upbringing of children and youth in order to develop optimal models of self-realization of the individual. Purposeful activities in this area of schooling also contribute to meeting the creative needs and requests of teachers and the study, systematization and promotion of best pedagogical experience. In order to gain students - future teachers - knowledge of trends in pedagogical ideas and educational activities of Ukrainian writers in Western Ukraine in the late XVIII - 30's of the twentieth century. The main tasks should be singled out - an objective analysis of the retro-experience of trends in pedagogical ideas and educational activities of Ukrainian writers of Western Ukraine in the period under study, coverage of the practice of this process in education, extracurricular, public education. Pedagogical reality dictates a change in views on the content and features of education and competencies that must be mastered by future teachers, taking into account the tasks of the school in understanding the content characteristics of education, upbringing and development of students, as well as systematizing pedagogical ideas and generalizing the experience of Ukrainian writers. - the first third of the twentieth century to highlight the educational potential of their creative heritage in the context of reforming the Ukrainian education system. Keywords: competence, pedagogy, tendencies, education system, Western Ukraine, education, upbringing, schooling.